The Pine seed bug (Leptoglossus occidentalis Heidemann) already in the western Forest-Steppe of Ukraine - Stiurko, M.O.; Korpita, N.M.; Ovchinnikova, O.P.; Alokhin, V.V.; Kovalchuk, O.I. (Quarantine and plant protection, 2026)
Goal. To record the presence and confirm the migration across Ukraine of the invasive pest, the western conifer-seed bug (Leptoglossus occidentalis Heidemann), and to document the expansion of its range and damage in orchards, parks and forests in the Lviv region. Methods. The presence of the pest was determined through phytosanitary monitoring using methods recommended for the detection of new invasive harmful organisms during surveys of garden, park and forest plantations. Results. L. occidentalis was detected in pine stands in garden, park and forest plantations in the Lviv region. The presence of this invasive pest was recorded at the State Enterprise ‘Lviv Forestry’ and the State Enterprise ‘Zhovkva Forestry’. Conclusion. Invasive pest species are dangerous, especially their mass colonisation and migration across the territory. Leptoglossus occidentalis causes direct damage to more than 40 species of conifers. It feeds on young and mature cones, causing the loss or failure of seeds to form. This can lead to the death of a wide range of coniferous tree species, a decrease in the self-renewal capacity of forests, and a decrease in the amount of biological diversity in our country. At the state level, it is necessary to develop and implement protection measures against the western conifer-seed bug (L. occidentalis Heidemann) in order to preserve the productivity of coniferous tree plantations. For effective protection, it is necessary to thoroughly study the biology of this invasive pest, investigate which favourable environmental factors influence its spread across the territory, and not forget about the high adaptability of insects to environmental conditions.